Commonalities in false guilty plea cases - Redlich, Allison D. (Psychology, crime & law, 2025)
False guilty pleas, when innocent people are wrongfully convicted by pleading guilty, have beset criminal legal systems since the time guilty pleas came into existence. Today, of the nearly 3,300 exoneration cases catalogued by the National Registry of Exonerations (NRE), about 25% are wrongful convictions via guilty plea, with the remaining 75% by trial. In the present study, we code the known population of wrongful plea convictions, comparing them to the known population of wrongful trial convictions on numerous factors (e.g. dispositional and situational risk factors) to identify defining characteristics of false guilty plea cases. Overall, we found many notable differences. False guilty plea cases are four times more likely to involve a false confession and be the ‘no-crime’ type of wrongful conviction than trial cases. In contrast, trial cases were significantly more likely to involve eyewitness misidentification, forensic science errors, perjury or false accusations, and documented ineffective assistance of counsel claims than false guilty plea cases. Results shed much-needed light on the factors that associate with false guilty pleas.